Neuropathic Pain with Features of Complex Regional Syndrome in the Upper Extremity after Herpes Zoster. Issue 2 (21st January 2013) - Giménez‐Milà, Marc; Busquets, Carme; Ojeda, Antonio; Faulí, Adela; Moreno, Luis Alfonso; Videla, Sebastian
Abstract We report a case of a 73‐year‐old female who developed unbearable neuropathic pain after a herpes zoster episode. The pain persisted and could not be controlled despite multimodal analgesia. In addition to postherpetic neuralgia, myelitis and complex regional pain syndrome were diagnosed during the evolution of neuropathic pain. This complex neuropathic pain was resolved after sympathetic ganglion block.